A meta-analysis of Hodgkin lymphoma reveals 19p13.3 TCF3 as a novel susceptibility locus - Cozen, W; Timofeeva, M N; Li, D; Diepstra, A; Hazelett, D; Delahaye-Sourdeix, M; Edlund, C K; Franke, L; Rostgaard, K; Van Den Berg, D J; Cortessis, V K; Smedby, K E; et al. (Nature communications, 2014)
Recent genome-wide association studies (GWAS) of Hodgkin lymphoma (HL) have identified associations with genetic variation at both HLA and non-HLA loci; however, much of heritable HL susceptibility remains unexplained. Here we perform a meta-analysis of three HL GWAS totaling 1,816 cases and 7,877 controls followed by replication in an independent set of 1,281 cases and 3,218 controls to find novel risk loci. We identify a novel variant at 19p13.3 associated with HL (rs1860661; odds ratio (OR)=0.81, 95% confidence interval (95% CI) = 0.76-0.86, P(combined) = 3.5 × 10(-10)), located in intron 2 of TCF3 (also known as E2A), a regulator of B- and T-cell lineage commitment known to be involved in HL pathogenesis. This meta-analysis also notes associations between previously published loci at 2p16, 5q31, 6p31, 8q24 and 10p14 and HL subtypes. We conclude that our data suggest a link between the 19p13.3 locus, including TCF3, and HL risk.
Keywords: Male; lidé středního věku; studie případů a kontrol; Genome-Wide Association Study; senioři nad 80 let; Aged, 80 and over; Humans; transkripční faktory bHLH; Middle Aged; senioři; mužské pohlaví; mladiství; Aged; genetická variace; Case-Control Studies; lidské chromozomy, pár 19; celogenomová asociační studie; Genetic Predisposition to Disease; Hodgkin Disease; mladý dospělý; Adult; Young Adult; Chromosomes, Human, Pair 19; Adolescent; Hodgkinova nemoc; Basic Helix-Loop-Helix Transcription Factors; genetická predispozice k nemoci; dospělí; lidé; Genetic Variation